2021
DOI: 10.30773/pi.2021.0174
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Turkish Version of Generalized Anxiety Disorder Scale-Revised

Abstract: Objective This study aims to assess the psychometric values of the Generalized Anxiety Disorder Scale-Revised (GADS-R) which measures the intensity and duration of worry, various coping and avoidance strategies to cope with worrying, and positive and negative metacognitive beliefs about worrying.Methods 114 patients with generalized anxiety disorder and 198 healthy controls were included in the study. These patients were diagnosed according to DSM-IV TR, and the primary diagnosis of the patients was generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…GAD is an extremely commonly seen mental health problem that has a negative effect on quality of life. 13 The aim of this study was to analyze the serum S100B, 8-OHdG levels and TOS, TAS, and OSI values of patients newly diagnosed with GAD who had not started treatment, to be able to better understand the underlying neurobiological basis of the etiology of GAD. The study results showed that the S100B and 8-OHdG levels of the patients diagnosed with GAD were higher than those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…GAD is an extremely commonly seen mental health problem that has a negative effect on quality of life. 13 The aim of this study was to analyze the serum S100B, 8-OHdG levels and TOS, TAS, and OSI values of patients newly diagnosed with GAD who had not started treatment, to be able to better understand the underlying neurobiological basis of the etiology of GAD. The study results showed that the S100B and 8-OHdG levels of the patients diagnosed with GAD were higher than those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that these psychological factors are less strong predictors or that their impact on FCR may be mediated and moderated by other factors such as worry 35 . Moreover, although the levels of metacognitive beliefs of patients from this study were similar to those observed in cancer patients in other studies (e.g., 11,12,36 ), it should be noted that these scores were lower than those obtained by patients presenting other anxiety disorders (e.g., 37,38 ). Patients' levels of metacognitive beliefs may thus not be characterized as maladaptive.…”
Section: Discussionmentioning
confidence: 99%